Pengaruh Electronic Word of Mouth, Fear of Missing Out, dan Hedonic Shopping Motivation terhadap Impulse Buying Produk Blind Box pada Konsumen di Surabaya - Yesi Nabela Mia Arifan; Acep Samsudin (Universitas Nusantara PGRI Kediri, 2026)
Transformations in buying patterns are largely driven by the accelerated expansion of the digital marketplace together with the pervasive engagement in social networking platforms. This phenomenon is reflected in the increasing inclination toward spontaneous purchases of surprise-oriented products such as blind boxes. The present study examines how Electronic Word of Mouth, Fear of Missing Out, and Hedonic Shopping Motivation relate to impulse buying behavior among blind box consumers in Surabaya. A quantitative method adopting an associative framework guided the investigation. Primary information originated from an online survey distributed to 156 participants selected through purposive sampling. Statistical examination relied on multiple linear regression, accompanied by validity testing, reliability assessment, classical assumption testing, hypothesis evaluation, and coefficient of determination analysis. Empirical evidence confirms that Electronic Word of Mouth, Fear of Missing Out, and Hedonic Shopping Motivation simultaneously produce a statistically meaningful impact upon impulse buying behavior. When assessed separately, every independent variable likewise reveals a meaningful contribution, where Fear of Missing Out appears as the strongest predictor. An R² value of 0.807 indicates that 80.7% variation in impulse buying behavior is attributable to the proposed framework, whereas the remaining share stems from additional determinants not incorporated within the analytical model.